American literature : a Prentice Hall anthology - Emory Elliot;Linda K. Kerber;A. Walton Litz;Terence Martin (New Jersey : Prentice-Hall, 1991)
During the past 20 years, the field of American literature has been going through one of the most exciting periods in its development as a discipline. Todays literature courses and anthologies presents these earlier writings as more accurate beginnings of American Literature.
Part1. The European Colonization of the Americas: Through the Middle 18th Century -- Part2. The Age of Democratic Revolution: The Late 18th Century -- Part3. Progress and Crisis: The Early to Middle 19th Century .
Includes index.
Keywords: AMERICAN LITERATURE